Austria in the European Union: dynamic gains from integration and distributional implications. Issue 22 (21st July 2014) - Keuschnigg, Christian; Kohler, Wilhelm
Summary: Austria in the European Union Dynamic gains from integration and distributional implications This article proposes to measure the welfare effects of Austria's membership of the EU. In addition to the traditional sectoral reallocation effects of open trade, our computations take into account a number of effects not usually measured: expected capital accumulation, saving, and income redistribution across generations. EU membership involves trade integration (lower trade costs, a common external tariff), adopting the common agricultural policy, and membership contributions to the EU. The gains from trade integration and the adoption of the common agricultural policy are partly offset by the burden of contribution payments. The net welfare gain, measured in terms of an equivalent permanent income stream, is 1.24% of GDP. This aggregate figure masks sizeable distribution effects. As expected, agriculture is particularly hard hit. Moreover, membership has a tendency to favour the old as well as future generations at the expense of those entering economic life at the time of accession. We conclude that the ultimate gains from EU membership will depend on how these distribution issues are solved and how the budgetary cost is financed. —Christian Keuschnigg and Wilhelm Kohler